Efek penggunaan tepung tomat sebagai bahan pakan terhadap penampilan produksi burung puyuh - Kurniawan, David; Widodo, Eko; Natsir, M. Halim (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The purpose of this research was to examine the optimum level of tomato powder addition as feedstuff on performances of quail including feed intake, Hen Day Production (HDP), egg weight, egg mass, feed conversion and Income Over Feed Cost (IOFC). One hundred twenty laying quails with 90 days old were used as intense of research. Feedstuffs were corn, rice bran, soybean meal, fish meal, pollard, premix and tomato powder. The treatments were P0 = feed without tomato powderaddition; P1 = feed with 5% of tomato powder addition; P2 = feed with 10% of tomato powder addition; P3 = feed with15% of tomato powder addition. Each treatment was repeated six times. The variables measured were feed intake, HDP, feed conversion, egg weight, egg mass, and IOFC. Data were analyzed using Analysis of Variance of the Completely Randomized Design (CRD) and if treatments showed significant differences then it was continued by Duncanâ€™s Multiple Range Test (DMRT). Results found that addition of tomato powder in the quail feed has indicated a similar effect to the control particularly on feed intake, HDP, egg weight, egg mass, feed conversion, and IOFC.Â Keywords: Lycopene, egg production, feed conversion, IOFC